Contribution of oral narrative textual competence and spelling skills to written narrative textual competence in bilingual language-minority children and monolingual peers - Vettori, Giulia; Bigozzi, Lucia; Incognito, Oriana; Pinto, Giuliana (Frontiers in Psychology, 2022)
This study investigates the developmental pattern and relationships between oral narrative textual skills, spelling, and written narrative textual skills in monolingual and bilingual language minority (BLM) children L1-Chinese and L2-Italian. The aims were to investigate in monolingual and BLM children: (1) the developmental patterns of oral and writing skills across primary school years; (2) the pattern of relationships (direct and mediated) between oral narrative textual competence, spelling skills, and written narrative textual competence with age and socio-economic status (SES) taken under control. 141 primary school children from grades 2 to 5 in Centre Italy (44% BLM, 56 % monolinguals) aged between 7 to 11 years old (M-age = 8.59, SD = 1.13; 41% girls, 59% boys) obtained scores for oral and written narrative textual competence, spelling accuracy in dictation and in written texts. One way ANOVA and ANOVA with robust method (Welch test) analyses and Bonferroni’s correction show that BLM children had poorer spelling skills in dictation and written narrative textual competence (i.e., text structure) than their monolingual peers. After preliminary correlation analysis, the results of hierarchical regression show that the relationship between oral and written narrative textual competence is completely mediated by spelling accuracy in BLM children. These results suggest that adequate performance in written narrative textual competence depends on adequate spelling accuracy in writing stories. The Sobel test verified the power of this mediation. In monolinguals, the strongest predictor of written narrative textual competence is oral narrative textual competence. This relation is stronger in older children whose spelling skills are automatized. The identified pattern of relationships shows a complex network of oral and written processes. The scarce spelling skills characterizing BLM children may explain why spelling skills determine a low written narrative textual level. Scarce spelling skills absorb cognitive resources, hindering high-level cognitive processes that regulate narrative production. In monolinguals, the medium of writing does not impact narrative textual competence. Children’s oral narrative textual competence easily transfers into their written narrative productions. These findings have implications for the assessment and instruction of literacy skills in young BLM children and their monolingual peers.